Market Research to help guide the positioning and marketing of NUBS’ MBA programmes - Vahid, Ijaz Shahul Hameed (2020)
The MBA degree is perceived as a matter of prestige for top business schools across the globe. Demand for the MBA has been on the decline for the past five years in the United States; however the trend hasn’t been mirrored in Europe. As the number of accredited business schools increase throughout the globe, the market is becoming highly competitive and business schools are forced to re-think their marketing strategies to compete in attracting global talent. Covid-19 has further complicated the situation with travel restrictions dampening the demand. Business schools around the world are planning to deliver a blend of online and offline teaching for full-time MBA programmes starting from September 2020, whilst some other business schools like the University of Lancaster have altogether cancelled their full-time MBA programmes for 2020.